“วีรชน” ลาว : กรณีศึกษาผ่านงานเขียนประเภทชีวประวัติช่วง ค.ศ.1986-2010 - เมตตาริกานนท์ ดารารัตน์ (Journal of Humanities and Social Sciences (HUSOKKU), 2013)
บทคัดย่อ จากการศึกษา พบว่า พรรคประชาชนปฏิวัติลาวและรัฐเป็นแกนหลักสำคัญในการสร้างประวัติศาสตร์ งานเขียนทางประวัติศาสตร์ได้มีการตีพิมพ์เผยแพร่ออกมาเป็นจำนวนมากในช่วงหลังทศวรรษ1980 เป็นต้นมา ทั้งประวัติศาสตร์ชาติ ประวัติศาสตร์พรรค ประวัติศาสตร์กองทัพ ประวัติศาสตร์ท้องถิ่น รวมทั้งประวัติศาสตร์ประเภทชีวประวัติ โดยมีกรอบแนวคิดแบบสังคมนิยมและอุดมการณ์ชาตินิยมอยู่เบื้องหลัง สำหรับงานเขียนทางประวัติศาสตร์ประเภท ชีวประวัติของ “วีรชน” นั้นพบว่า หลังเปลี่ยนประเทศเป็นสังคมนิยม พรรคประชาชนปฏิวัติลาวและรัฐบาลลาวได้ยกย่องบุคคลและหน่วยงานให้เป็น “วีรชน” โดยแบ่งกลุ่มได้เป็น 4 กลุ่มคือ 1. วีรกษัตริย์ 2. วีรบุรุษ 3. วีรชนแห่งชาติ 4. นักรบแข่งขันแห่งชาติ ทั้งสี่กลุ่มนี้ได้รับการยกย่องและให้ความสำคัญที่แตกต่างกัน งานประเภทชีวประวัติเป็นอีกเครื่องมือหนึ่งที่พรรคและรัฐบาลลาวได้ใช้ในการเผยแพร่อุดมการณ์ทางการเมืองของตน นอกเหนือจากจุดมุ่งหมายเพื่อยกย่องเชิดชูเกียรติ “วีรชน” นี้แล้ว จุดมุ่งหมายหนึ่งที่สำคัญก็คือการปลูกฝังอุดมการณ์ชาตินิยมและแนวคิดสังคมนิยมนั่นเอง Abstract This case study found that the Lao People’s Revolutionary Party (LPRP) and the Lao government played key roles in creating Lao history. Since 1980, large volumes of Lao historical writings have been published for the public, ranging from national, party, army, and local histories to autobiographies. All of the writings are based on nationalistic and socialistic concepts. After the country changed to a socialistic system, autobiographies of “Heroes” in Laos were significantly influenced by the party and the government, which retained absolute power to classify whom should be written about and on what level of status. Institutes and persons who were great benefactors to Laos were honored as the country’s “Heroes”. The LPRP and the government classified the heroes into four groups: - Heroic Kings (Wirakasat) ”(The kings that have been admired “Heroes of the Kings” - Presidential Heroes (Wiraburut) - National Heroes (Wirachon Haeng Chat) (Important leaders who have been honored as “National Heroes) - National Warriors (Winners of Competitive Battles) (Nak Rop Khaeng Khan Haeng Chat). These four groups were given honors that differed in their level of importance. Thus, autobiographies, in addition to honoring people, became another tool that the LPRP and Lao government used to propagate their political ideology.